Ocorrência de distúrbios da gestação, parto e puerpério em vacas leiteiras - Camargos, Aline Sousa; Gioso, Marilu Martins; Reis, Luis Souza Lima de Souza [UNESP]; Costa, Isadora Frason [UNESP]; Ferraz, Myrna Campos [UNESP]; Oba, Eunice [UNESP] (My University, 2013)
This study aimed to diagnose and quantify the occurrence of pregnancy, parturition and puerperium disorders in dairy cattle. Ten small dairy farms have had their herds monitored from January to December, in southeast Brazil. Reproductive failures were studied in 380 adult Holstein-Zebu cows. All cows were submitted to clinical and reproductive examinations every fifteen days, when disorders of pregnancy, parturition and puerperium were diagnosed and recorded. During the study were observed 1.84% of fetal dystocia, 3.68% of fetopelvic disproportion, 7.10% of retained placenta, 0.53% of prolonged gestation, 3.95% of uterine infection, 0.53% of prolapsed vagina and 0.53% of prolapsed uterus. The farms did not differ significantly for anyone of the variables studied by the Chisquare test (P ≥ 0.05).

Este estudo objetivou diagnosticar e quantificar a ocorrência de distúrbios da gestação, parto e puerpério em vacas leiteiras. Dez pequenas propriedades foram monitoradas de Janeiro a Dezembro, na região sudeste brasileira. As falhas reprodutivas foram estudadas em 380 vacas adultas mestiças Holandês-Zebu. Todos os animais foram submetidos a exames clínicos e reprodutivos quinzenalmente, quando os distúrbios da gestação, parto e puerpério foram diagnosticados e registrados. Durante o estudo, foram observados 1,84% de distocia fetal; 3,68% de desproporção fetopélvica; 7,10% de retenção de placenta; 0,53% de gestação prolongada; 3,95% de infecção uterina; 0,53% de prolapso vaginal e 0,53% de prolapso uterino. As propriedades não diferiram estatisticamente em nenhuma das variáveis estudadas pelo teste do Qui-quadrado (P ≥ 0,05).
Occurring disorders of pregnancy, birth and dairy cows in puerperium
Keywords: Dystocia; Retained placenta; Prolonged gestation; Uterine infection; Prolapses; Distocia; Retenção de placenta; Gestação prolongada; Infecção uterina; Prolapsos